Development of robotic arm system replica for arranging books in library / Ahmad Faris Irfan Mohd Fazuli - Mohd Fazuli, Ahmad Faris Irfan (2023)
Books arrangement and organizing is a fundamental works in places like library when there are hundreds of it to be handled with. Doing it manually can lead to an error such as misplacement, uneven spacing and other issues. To overcome this problem, this study goal is to develop a replica of robotic mechanical arm system to help arranging books in more efficient way. By using a model by Arduino, the study focus will be to design a system that can transport books from location 1 to location 2 A few experiments will be conduct to measure its effectiveness on arranging books and to measure the system's limits. The success of this project will make things easier for librarian specifically and maybe others fields that involving with books such as bookstores.